The citizen self and aboriginal “other” : notions of citizenship and aboriginality in British Columbian social studies education, 1945-present - Birkeland, Nicole (Author); Shelvey, Bruce (Thesis supervisor); Etherington, Matthew (Second reader); Barman, Jean (External examiner); Trinity Western University SGS (Degree granting institution) (Trinity Western University, 2013)
Social studies education in British Columbia from the 1940s until present has upheld active citizenship as a central objective of the program. While citizenship is never clearly defined, generally it has been assumed that through a process of self-actualization students come to know their rights and responsibilities as Canadian citizens. Problematically, these notions of citizenship have shaped the narration of Aboriginality within social studies education. Aboriginality has been represented in learning outcomes and resources materials within a progressive Canadian metanarrative, creating inaccurate and uninformed characterizations of Aboriginal peoples. Overall, social studies education has had a negative impact on the First Nations-Canadian relationship. However, social studies education could assist in developing more positive relationships. Engaging students in transformed historical study that fosters questioning, examines narrative choices, sees negotiation and interaction, recognizes and honours difference, and allows for dialogue, may foster more promising relationships in the future.